Antarctic outlet glacier mass change resolved at basin scale from satellite gravity gradiometry. Issue 16 (20th August 2014) - Bouman, J.; Fuchs, M.; Ivins, E.; van der Wal, W.; Schrama, E.; Visser, P.; Horwath, M.
Abstract The orbit and instrumental measurement of the Gravity Field and Steady State Ocean Circulation Explorer (GOCE) satellite mission offer the highest ever resolution capabilities for mapping Earth's gravity field from space. However, past analysis predicted that GOCE would not detect changes in ice sheet mass. Here we demonstrate that GOCE gravity gradiometry observations can be combined with Gravity Recovery and Climate Experiment (GRACE) gravity data to estimate mass changes in the Amundsen Sea Sector. This refined resolution allows land ice changes within the Pine Island Glacier (PIG), Thwaites Glacier, and Getz Ice Shelf drainage systems to be measured at respectively −67 ± 7, −63 ± 12, and −55 ± 9 Gt/yr over the GOCE observing period of November 2009 to June 2012. This is the most accurate pure satellite gravimetry measurement to date of current mass loss from PIG, known as the "weak underbelly" of West Antarctica because of its retrograde bed slope and high potential for raising future sea level.